Comparative study of outcome of Postdated Pregnancy of Primaegravida and Multigravida Patients - Begum, Arzu Manth Ara; Kobra, Khodeza Tul; Begum, Rashida (Journal of Dhaka National Medical College & Hospital, 2014)
Background : Postdated pregnancy is a high risk pregnancy in obstetric situation because the perinatal morbidity and mortality exceed that of term pregnancies. According to the definition provided by the WHO and International Federations of Obstetrics and Gynaecology, a prolonged pregnancy is one that exceeds 294 days or 42 weeks from the first day of last menstrual period and postdated pregnancy is a condition which has passed beyond the expected date of delivery. Objectives:To reduce the maternal and perinatal morbidity and mortality and to reduce the incidence of operative delivery in primigravida and multigravida patients in post dated pregnancy. Materials and methods :The study was carried out from January to June, 2012 in the department of Obstetrics and Gynaecology, Dhaka National Medical Institute Hospital (DNMIH) Dhaka. Out of 206 women with postdated pregnancy, admitted during the study period in the obstetric ward of DNMIH, 80 women who fulfilled inclusion criteria, constituted the study population. Results :In the present study out of 80 women with postdated pregnancy, 42(52.5%) were primaegravida and 38(47.5%) were multigravida. All the women of primaegravida group belonged to age group <30 yrs 42(100%) compared to 26(68.4%) multigravida. In this study, significantly more multigravida achieved normal vaginal delivery (19% primaegravida and 47.4% multigravida). Higher number of primaegravida (81%) delivered by LUCS compared to multigravida (47.4%) Postdated pregnancy did not affect significantly on the fetal weight between primaegravida and multigravida group (mean SD 2.93± 0.31 vs. 3.01±0.40 kg). However Apgar score was significantly lower in multigravida group (mean±SD 6.61±1.05) compared to primaegravida group (mean SD 7.19± 1.10). Maternal complications were higher among primaegravida compared to multigravida. In the present study, there was no neonatal or maternal death. J. Dhaka National Med. Coll. Hos. 2014; 20 (02) : 16-20